Spatial-temporal spectroscopy characterizations and electronic structure of methylammonium perovskites - Liu, Zhaoyu; Bhamu, K. C.; Luo, Liang; Shah, Satvik; Park, Joong-Mok; Cheng, Di; Long, Men; Biswas, Rana; Fungara, F.; Shiner, Ruth; Shiner, Joseph; Vela, Javier; et al. (MRS Communications, 2018)
Using time-resolved laser-scanning confocal microscopy and ultrafast optical pump/THz probe spectroscopy, we measure photoluminescence (PL) and THz-conductivity in perovskite micro-crystals and films. PL quenching and lifetime variations occur from local heterogeneity. Ultrafast THz-spectra measure sharp quantum transitions from excitonic Rydberg states, providing weakly bound excitons with a binding energy of similar to 13.5 meV at low temperatures. Ab-initio electronic structure calculations give a direct band gap of 1.64 eV, a dielectric constant of similar to 18, heavy electrons, and light holes, resulting in weakly bound excitons, consistent with the binding energies from the experiment. The complementary spectroscopy and simulations reveal fundamental insights into perovskite light-matter interactions.